Housing Affordability and Housing Policy in Urban China - Yang, Zan.; Chen, Jie.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book provides a comprehensive analysis of housing affordability under the economic reforms and social transformations in urban China. It also offers an overall review of the current government measures on the housing market and affordable housing policies in China. By introducing a dynamic affordability approach and residual income approach, the book allows us to capture the size of the affordability gap more accurately, to better identify policy targets, and to assess the effectiveness of current public policy. The unique database on urban household surveys and regional information on affordable housing projects serve to strengthen the analysis. The book offers theoretical and empirical insights for in-depth affordability studies and helps readers to understand the social impacts of market reforms and the role of government on the Chinese housing market.
Introduction -- Housing Reform and the Housing Market in Urban China -- Theoretical Background: Affordability and Its Measurement -- Housing Affordability in Urban China: National Study -- Housing Affordability in urban China: Regional Study -- Effects of Housing Policy on Affordability -- Financing Affordable Housing through Compulsory Savings -- Conclusion.
Keywords: Economics; Economic policy; Economics/Management Science; Economic Policy